STRUCTURAL FEATURES OF THE NORMAL MAJOR SALIVARY GLANDS STROMA OF RATS - Volkov, K.S.; Yeroshenko, H.A.; Koptev, M.M.; Kramarenko, D.R. (World of Medicine and Biology, 2017)
The aim of the study was to determine the stroma structural features in the major salivary glands of rats in normal state. The study was carried out on 20 adult white male Wistar rats with body weight 260-300 grams, aged 10-12 months. Histological examination of the parotid stroma determined that the intralobular connective tissue was represented by amorphous substance, collagen fibers and fibroblast processes between adjacent terminal parts. The fibroblast bodies were located in the nodular interstitial compartments − the contact points of 3-4 terminal parts of the gland lobules as well as collagen fibers and blood vessels of the hemomicrocirculatory bed − capillaries and postcapillaries. Postcapillaries and venules were revealed in periductal connective tissue. The local protective barrier of the major salivary glands stroma in rats is predominantly represented by plasmocytes and macrophages in the interacinar interstitium as well as macrophages and mast cells in the periductal connective tissue.